SIKOPING SEBAGAI PENANGANAN DEPRESI MASYARAKAT PENDERITA DIABETES MELITUS - Fijianto, Dwi; Faradisi, Firman; Wirotomo, Tri Sakti (Jurnal Ilmu Keperawatan Komunitas, 2023)
The prevalence of diabetes mellitus (DM) is increasing every year and is a trigger for psychosocial problems such as depression. Depression further worsens the condition of uncontrolled blood sugar and prolongs the healing time of wounds caused by DM. So that the coping strategies used by sufferers must be fast and precise so that depression can be controlled and finally blood sugar is controlled and wound healing becomes faster. The research focuses on a new mobile application in the form of the SIKOPING digital application (coping strategy system) as a guide for DM sufferers in reducing depression that occurs due to DM disease. The results of the research are in the form of digital media, a guide to coping strategies to reduce depression in DM sufferers. The study aimed to find out whether the use of the SIKOPING digital application has any influence in using the right coping strategy and reducing depression in DM sufferers. The research method uses a Quasi Experiment design with a pre-post test approach without a control group. The data normality test with Shapiro Wilk obtained a significance value of <0.05, which means that the data is not normally distributed, so the statistical test uses the Wilcoxon test. Number of respondents: The research obtained 43 respondents. The results of the study obtained a p-value of 0.000 <0.05, which means that there is an influence between the application of coping strategies using the SIKOPING application on the decrease in the level of depression in DM sufferers